Sistem Monitoring Untuk Mesin Pelayanan Pelanggan (Studi Kasus Di Etisalat Corporation, Abu Dhabi) - Santoso, Bambang (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Customer service machines for a telecom operator are tools to prevent customers from churning (switching to another provider). So it is important to know the functional of these machines from time to time. These machines also help telecom operators to reduce the number of branch offices because the machines can indicate the existence of the operator without any branch office. Opening a branch office will cost more than machines because it has to rent a bigger place and more employees and equipments needed. However, sometimes these customer service machines have faults that some or all services cannot function well. For this the telecom operator requires another tool that will monitor the functional of the customer service machines. Another device called a monitoring system is required at all time to 'see' the existence of the machines. The monitoring system unfortunately cannot repair machines. If one machine is known to not function properly, then a technician is required to come and fix the machine. The monitoring system at any given interval polls the machines and requests its status. Afterward it writes the status in the database. Consequently, it is required to build an application interface that reads the database. The technicians can at any time see that status through an application program to find out if any machine requires attention. At the end of the week or at the end of the month technicians’ supervisors can obtain uptime statistics of the machines. Statistics are required as a base of observation and review for future service improvements.